Effects of ankylosing spondylitis on cardiovascular disease: aMendelian randomization study - Xiao, Lu; Lin, Shudian; Zhan, Feng (Frontiers in Genetics, 2024)
Objective Accumulating evidence suggests that patients with ankylosing spondylitis (AS) have an elevated risk for cardiovascular disease (CVD) and cardiovascular death, however, whether AS has causal effects on the risk of CVD is unclear.Two-sample Mendelian randomization (MR) was utilizedto examine the probable causal link between them. Methods Summary statistics from publicly released genome-wide association studies (GWAS) was used to perform MR analyses. Genetically predicted AS was selected as the exposure variable from published GWAS meta-analyses. CVD was adopted as the outcome variable. The inverse variant weighted method was employed to obtain the casual estimates. The robustness of the results was also examined by evaluating the pleiotropy and heterogeneity of single-nucleotide polymorphisms. Results According to MR analyses, genetic susceptibility to AS was associated with a high risk of heart failure and ischemic stroke, while negativelygenetic susceptibility was found between AS and peripheral atherosclerosis. No statistical relationship was found between AS and venous thromboembolism, atrial fibrillation, coronary atherosclerosis, and valvular heart disease. Sensitivity analysis showed no evidence of horizontal pleiotropy or heterogeneity. Conclusion The present study suggests that AS exerts causal effects on the risk of CVD, including heart failure, ischemic stroke, and peripheral atherosclerosis.